Analysis of Average Length of Schooling of Indonesian Citizens in the Future Using Markov Chains - Riza Adrian Ibrahim; Sivaperumal Sampath (International Journal of Ethno-Sciences and Education Research, 2022)
Based on data from the Central Bureau of Statistics of the Republic of Indonesia, the average length of schooling of Indonesian citizens is continuously increasing every year. This increase is predicted to continue in the future. However, it has yet to be discovered how the increasing rate in the average length of schooling will occur. Therefore, this study aims to analyze the increasing rate of the average length of schooling of Indonesian citizens in the future. The data used is the average length of schooling of Indonesian citizens from 2010 to 2021. The analytical method used is the discrete-time Markov chain. Furthermore, the states representing the increasing rate in the average length of schooling used are divided into two: the increasing rate in the average length of schooling that is smaller and larger than the average. Based on the analysis results, the probability that the increasing rate in Indonesian citizens' average length of schooling will be less than the average in the future is 0.4. In contrast, the probability that the increasing rate in Indonesian citizens' average length of schooling will be greater than the average in the future is 0.6. It indicates that Indonesian citizens will have a high education level in the future. The results can be used as the future education state projection of Indonesian citizens so that it can be accompanied by empowerment.